PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE PICTURE AND PICTURE TERHADAP HASIL BELAJAR DAN KREATIVITAS SISWA KELAS X SMKN 1 BLEGA PADA MATA PELAJARAN IPAS - Syaifullah, Moh.; Muhajir; Huda, Nuril (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The picture and picture type cooperative learning model is one of the effective teaching strategies in improving students' understanding and learning activity. This model is part of the visual learning model, which emphasizes the use of images or visuals as the main aid in the learning process. This study aims to determine the effect of the picture and picture type cooperative learning model on the learning outcomes and creativity of class X students of SMKN 1 Blega in the Science Subject. The data collection method uses an experimental design in the form of pretest and posttest instruments to measure student learning outcomes, and observations in the form of questionnaires to measure student creativity. The data analysis method uses Descriptive Test, Instrument Test (Validity Test, and Reliability Test), Classical Assumption Test (Normality Test, and Homogeneity Test), and Hypothesis Test. Based on the results obtained, it can be seen that in the pretest and posttest the learning outcomes obtained a significant value of 0.000 <0.05, these results indicate that there is a significant difference in learning outcomes before and after being given the Picture and Picture type cooperative learning model. Meanwhile, in the pretest and posttest, creativity obtained a significant value of 0.000 <0.05. These results indicate that there is a significant difference in creativity before and after being given the Picture and Picture Cooperative learning model. The conclusion of this study is that the Picture and Picture Cooperative learning model is able to improve learning outcomes and creativity of students at SMKN 1 Blega in the subject of IPAS.